DINAMIKA KELOMPOK TANI PADA USAHATANI PADI SAWAH DI DESA PEATOA KECAMATAN LOEA KABUPATEN KOLAKA TIMUR - Haslinda; Awaluddin Hamzah; Sukmawati Abdullah (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This study aims to examine the dynamics of farmer groups engaged in rice paddy farming in Peatoa Village, Loea District, East Kolaka Regency. The population under investigation consisted of all wet-rice farmers who were members of farmer groups in Peatoa Village, with a total of 54 wet-rice farmers. The sample was determined using the census method, whereby the entire population was included in the study, resulting in a research sample of 54 respondents. This research employs a quantitative approach. Data were gathered through survey methods, interviews, and documentation via media in the form of questionnaires. The data were processed using a quantitative descriptive method with the class interval formula and Spearman Rank correlation, with the assistance of SPSS software. The results indicated that the dynamics of paddy rice farmer groups in Peatoa Village had a positive impact on farm development. The majority of farmer group members shared similar goals. Group structure involved the division of tasks and responsibilities among members. The farmer groups demonstrate a high level of group task function. The farmer group coaching is progressing well. Each group member exhibits high levels of cohesion, which reflects effective unity and cohesiveness in managing rice paddy farming. A positive group atmosphere enhances cooperation, engagement, and productivity. The level of farmer group activity is an important factor in farm success. Overall, the farmer group dynamics in Peatoa Village show positive patterns, providing insights for agricultural policy development and community development in the region. Further enhancements to the dynamics of farmer groups may also be considered to enhance the productivity of wet-rice farming.